1995
DOI: 10.1172/jci118317
|View full text |Cite
|
Sign up to set email alerts
|

Why there is an IRS.

Abstract: Insulin regulates the expression of at least 100 genes (1). This major action of the hormone is important for normal metabolism but gains added significance in view of the fact that insulin resistance is the cornerstone of genetic diseases such as noninsulin-dependent diabetes mellitus and obesity. The possibility that faulty regulation of gene expression by insulin could result in disease is now given credence by the observations reported by Li et al. (2) in this issue of The Journal.Hypertriglyceridemia (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…We have identified two important genes, (namely, Rad and the p85 ␣ regulatory subunit of phosphatidylinositol-3-kinase) that can be added to the growing list of the genes controlled by insulin. Since the products of these genes, in particular PI-3K, play a crucial role in the insulin mechanism of action, our findings strengthen the possibility that altered regulation of gene expression by insulin could result in insulin resistance (39). The methodology developed here allowing a wide screening of mRNA levels represents a valuable tool to test this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…We have identified two important genes, (namely, Rad and the p85 ␣ regulatory subunit of phosphatidylinositol-3-kinase) that can be added to the growing list of the genes controlled by insulin. Since the products of these genes, in particular PI-3K, play a crucial role in the insulin mechanism of action, our findings strengthen the possibility that altered regulation of gene expression by insulin could result in insulin resistance (39). The methodology developed here allowing a wide screening of mRNA levels represents a valuable tool to test this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…Scanning this region revealed three putative Foxo1 binding sites (core motif T(G/A)TTT) (Fig. 3A), which are usually named insulin response sequences (IRSs) (18,31). The results of the transient transfection study showed that mutation of IRS1 or IRS3 significantly decreased the basal adiponectin promoter activity (Fig.…”
Section: Foxo1mentioning
confidence: 99%